2023
DOI: 10.1186/s13098-022-00945-3
|View full text |Cite
|
Sign up to set email alerts
|

2022: Position of Brazilian Diabetes Society on exercise recommendations for people with type 1 and type 2 diabetes

Abstract: Introduction For individuals diagnosed with diabetes mellitus, the practice of properly oriented physical exercises brings significant benefits to the individual's health and is considered an indispensable tool for metabolic management. The individualization of exercise routines is an essential aspect for therapeutic success, despite the need to consider some general recommendations. This review is an authorized literal translation of the Brazilian Society of Diabetes (SBD) Guidelines 2021–2022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…This study aimed to produce a literature synthesis, through a rapid review, on the effects of aerobic, resistance, and combined physical training variables on glycemic control in adults with type 2 Diabetes Mellitus. There is a strong body of evidence on the therapeutic effect of physical exercise on the prevention and treatment of T2DM ( 13 , 16 , 21 , 42 ). However, previous studies have reported important heterogeneity in adherence rates and a low rate of patients with diabetes meeting the minimum amount of exercise recommended by guidelines ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to produce a literature synthesis, through a rapid review, on the effects of aerobic, resistance, and combined physical training variables on glycemic control in adults with type 2 Diabetes Mellitus. There is a strong body of evidence on the therapeutic effect of physical exercise on the prevention and treatment of T2DM ( 13 , 16 , 21 , 42 ). However, previous studies have reported important heterogeneity in adherence rates and a low rate of patients with diabetes meeting the minimum amount of exercise recommended by guidelines ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise should be tailored to meet the specific personal and clinical needs of each patient ( 11 ). An individualized exercise program is crucial for therapeutic success, although there are general guidelines ( 9 , 12 16 ). Properly prescribed and executed physical exercise offers significant benefits to individuals with T2DM, serving as an effective tool for metabolic management and a non-pharmacological strategy for the prevention and treatment of T2DM in adults and older adults ( 9 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…(Jauregui y López, 2015). Así, abogamos también por la recomendación de la Sociedad Brasileña de Diabetes, (2022) (Pereira et al, 2023) en relación al ejercicio en individuos con DMT1, sugiriendo que aquellos sujetos dependientes de insulina como tratamiento terapéutico deben controlar adecuadamente los niveles de glucemia antes, durante y después de las sesiones de ejercicio para minimizar los incidentes como la hipoglucemia.…”
Section: Ejercicio Aeróbico (Ea)unclassified
“…Si el ejercicio se torna muy intenso, >85% de la frecuencia cardíaca máxima (FC máx), el metabolismo anaeróbico es el que suministra la mayor parte de la energía (Yardley et al, 2013), en éste sentido, se ha propuesto que los sprints están asociados con aumentos de hormonas contrarreguladoras (catecolaminas, glucagón, hormona del crecimiento) que pueden actuar para aumentar los niveles de glucosa (Cockcroft et al, 2020), de manera que esfuerzos predominantemente anaeróbicos, a menudo conducen a situaciones de hiperglucemia durante el ejercicio y poco después de su culminación (Campbell et al, 2015), precisamente por su efecto hiperglucemiante se sugiere que incluir alguna actividad breve de alta intensidad (5-15 s) en una sesión de EA podría ser un enfoque eficaz para contrarrestar la hipoglucemia (French et al, 2007). Al mismo tiempo, el ER genera incremento de estas hormonas contrarreguladoras (Cockcroft et al, 2020;Petschnig et al, 2020), que de manera similar a la inclusión de sprints, podría ayudar a estabilizar la glucosa en sangre, quedando demostrado que realizar ER antes (Yardley et al, 2013) o después de una sesión de EA tiene efectos protectores (Cockcroft et al, 2020).…”
Section: Ejercicio Anaeróbicounclassified
“…While critically ill patients may need intravenous insulin infusion therapy, and pharmacotherapy is both marketed intently and popular, 20 these approaches do not truly change the underlying modifiable or behavioral causes or contributors to the condition at all effectively. 21 Safer and available to all adults even in low income countries, the adoption of moderate exercise appears highly justified in this regard if one considers its value for both diabetes and osteoarthritis care, its wide ranging approaches, its simplicity, low cost, and the observation most cases of Type 2 diabetes can be managed by blood glucose monitoring, diet, and moderate exercise, 3,10,22 with exercise as the most promising approach. It is also the preferred approach for countering osteoarthritis pain and for possible sustained weight control.…”
Section: Introductionmentioning
confidence: 99%